Hubungan Kadar Hemoglobin Dengan Ketahanan Kardiorespirasi Pada Anak Sekolah Dasar - Agus Sudrajat; Catur Retno Lestari; Lisa Istarofah (Puslitbang Sinergis Asa Professional, 2022)
The degree of health of a person's body has decreased which consists of one of the supporting body health, namely cardiorespiratory health or called the degree of maximum oxygen quantity (VO2Max). Children who do less physical activity in the future can experience cardiorespiratory problems such as shortness of breath, heart attack, chest pain, and stroke, because cardiorespiratory fitness increases insulin sensitivity, glucose transport, improves nervous system function and lowers heart rate. This study aims to to determine the relationship between hemoglobin levels and cardiorespiratory resistance (VO2max) in elementary school children. This study is a correlational study on the subjects of elementary school children aged 10-12 years. and multistage random sampling. Measurement of physical fitness level using the Harvard step test method, pulse rate and VO2max were measured using an oximeter, hemoglobin level data using the cyanmeth method. The statistical test used was the Shapiro-Wilk test and the regression estimation curve test was used to determine the relationship between variables. The results of measuring cardiorespiratory endurance (VO2max) by measuring cardiorespiratory function using the Harvard step test showed that on average elementary school children had less cardiorespiratory endurance (49.01 ± 15.16). The results of measuring the hemoglobin level of the subjects showed that the average hemoglobin level was normal (11.03±0.83 mg/dl). The normality test of the data used, namely Shapiro-Wilk, shows a significance of 0.000 (<0.05), which means that the data is not normally distributed. The results of the analysis obtained using the regression estimation curve obtained a correlation coefficient of 0.46 with a significance of 0.786 (p>0.05). The conclusion in this study is that there is no relationship between hemoglobin levels and cardiorespiratory endurance (VO2max) in elementary school children. The importance of providing a balanced nutritional intake, a balanced diet and activity can increase hemoglobin and VO2max levels in elementary school children.